Makrozoobenthos sebagai Bioindikator Kualitas Air di Sungai Paneki Desa Pombewe Kabupaten Sigi - Nidya Khusni Fatul Janah; Abd. Rauf; Bustamin Bustamin (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Water is a source of life for humans. The need for water often makes humans unaware that their activities can trigger the entry of pollutants into water bodies. These pollutants can degrade river water quality. Water quality refers to the condition of water based on its physical, chemical, and biological characteristics. Water quality can be analyzed based on the presence of aquatic organisms intolerant to pollutants. The objective of this study is to describe the water quality of Paneki River based on the presence of Macrozoobenthos organisms as water bioindicators. This research is a quantitative descriptive study using a line transect sampling technique at three purposively selected stations. The results showed that Macrozoobenthos found belonged to 11 families: Gecarcinucidae, Coenagrionidae, Baetidae, Physidae, Hydropsychidae, Heptageniidae, Gomphidae, Lumbricidae, Palaemonidae, Philopotamidae, and Naucoridae. The calculation of water quality analysis based on the Family Biotic Index at station I was 4.07, and station II was 4.09, indicating both stations are classified as excellent water quality with slight pollution from organic matter. Station III scored 4.42, classified as good water quality with some pollution from organic matter.